Superconducting properties and μSR study of the noncentrosymmetric superconductor Nb0.5Os0.5. (22nd January 2018) - Singh, D; Barker, J A T; Thamizhavel, A; Hillier, A D; Paul, D McK; Singh, R P
Abstract: The properties of the noncentrosymmetric superconductor ( α - M n structure) Nb0.5 Os0.5 have been investigated using resistivity, magnetization, specific heat, and muon spin relaxation and rotation ( μ SR) measurements. These measurements suggest that Nb0.5 Os0.5 is a weakly coupled ( λ e − p h ∼ 0.53 ) type-II superconductor ( κ G L ≈ 61 ), having a bulk superconducting transition temperature T c   =  3.07 K. The specific heat data fits well with the single-gap BCS model indicating nodeless s-wave superconductivity in Nb0.5 Os0.5 . The μ SR measurements also confirm s -wave superconductivity with the preserved time-reversal symmetry.